Efficacy and Mechanism-of-Action of a Novel Superagonist Interleukin-15: Interleukin-15 Receptor αSu/Fc Fusion Complex in Syngeneic Murine Models of Multiple Myeloma - Xu, Wenxin; Jones, Monica; Liu, Bai; Zhu, Xiaoyun; Johnson, Christopher B.; Edwards, Ana C.; Kong, Lin; Jeng, Emily K.; Han, Kaiping; Marcus, Warren D.; Rubinstein, Mark P.; Rhode, Peter R.; et al. (Cancer research (Chicago, Ill.), 2013)
ALT-803, a complex of an interleukin (IL)-15 superagonist mutant and a dimeric IL-15 receptor αSu/Fc fusion protein, was found to exhibit significantly stronger in vivo biologic activity on NK and T cells than IL-15. In this study, we show that a single dose of ALT-803, but not IL-15 alone, eliminated well-established 5T33P and MOPC-315P myeloma cells in the bone marrow of tumor-bearing mice. ALT-803 treatment also significantly prolonged survival of myeloma-bearing mice and provided resistance to rechallenge with the same tumor cells through a CD8+ T-cell–dependent mechanism. ALT-803 treatment stimulated CD8+ T cells to secrete large amounts of IFN-γ and promoted rapid expansion of CD8+CD44high memory T cells in vivo. These memory CD8+ T cells exhibited ALT-803–mediated upregulation of NKG2D (KLRK1) but not PD-1 (PDCD1) or CD25 (IL2RA) on their cell surfaces. ALT-803–activated CD8+ memory T cells also exhibited nonspecific cytotoxicity against myeloma and other tumor cells in vitro, whereas IFN-γ had no direct effect on myeloma cell growth. ALT-803 lost its antimyeloma activity in tumor-bearing IFN-γ knockout mice but retained the ability to promote CD8+CD44high memory T-cell proliferation, indicating that ALT-803–mediated stimulation of CD8+CD44high memory T cells is IFN-γ–independent. Thus, besides well-known IL-15 biologic functions in host immunity, this study shows that IL-15–based ALT-803 could activate CD8+CD44high memory T cells to acquire a unique innate-like phenotype and secrete IFN-γ for nonspecific tumor cell killing. This unique immunomodulatory property of ALT-803 strongly supports its clinical development as a novel immunotherapeutic agent against cancer and viral infections. Cancer Res; 73(10); 3075–86. ©2013 AACR.